Membangun Ekonomi Sirkular: Pelatihan dan Pendampingan Daur Ulang Sampah Plastik bagi Masyarakat Desa - Wahyuningsih, Yusminar; Pratisti, Cahyani; Yuniastuti, Rina Milyati; Wijayanti, Yoan Budi (Muttaqien Publishing Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR. KH.EZ. Muttaqien Purwakarta, 2025)
One of the potential objects to be developed in the circular economy era is household plastic waste. Housewives around the Batu Putuk tourist attraction have plastic waste from household that have not been managed properly. This causes several losses such as odor and visual pollution and becomes a source of disease. This is because housewives do not know the dangers of plastic waste and how to process plastic waste. This service activity aims to provide understanding and increase awareness about the dangers of plastic waste and various types of processing of plastic waste, as well as train housewives to make creations from PET-type plastic waste into valuable products. The method used was awareness and increased understanding, training, and counseling to 20 housewives around the Batu Putuk Village tourist attraction. There was an increased understanding of the types of plastic waste and how to process it. There was an increased skill in making creations from plastic waste into goodie bags, tissue holders, wallets, and flowers. The driving factor for the program's success is the participants who already have sewing and patternmaking skills. In contrast, the inhibiting factor is the minimal sewing skills. Participants were also interested in creating an association to make plastic waste.